Experience of Mothers Having Preterm Newborns in Neonatal Care Units - Shrestha, Tumla; Singh, Ajanta; Bhattarai, Saraswoti Kumari Gautam; Raut, Kalpana Silwal (Journal of Karnali Academy of Health Sciences, 2020)
Background: Preterm births are vulnerable to morbidities and require hospitalization in the neonatal care unit (NCU). The situation is stressful for mothers influencing their attachment and care to the newborns. Therefore, this study was conducted to explore the experience of mothers having preterm newborns in NCU.Methods: The qualitative study was conducted among purposively selected 13 mothers of NCU admitted preterm infants at Tribhuvan University, Teaching Hospital. Data was collected using in-depth interview. Colaizzi content analysis method was used for data analysis.Results: Among 13 mothers, 8 were primipara, 25-30 years, homemakers; 6 had Bachelor or above education; 11 had ANC visit > 4 times. Ten infants were very preterm (< 32 weeks gestational age), 11 have very low birth weight (< 1500 gram), 9 born by caesarian section and stayed NICU for 7-14 days. Study identified 5 themes and 18 subthemes: loss of control (fear and anxiety, distress towards pain and suffering, guilt feeling, hopelessness); sense of difference (newborn’s appearance, needs and problems, breastfeeding and parental roles); care of newborn (trust to nurses, confidence and emotional attachment with care involvement,), support for coping (support from family, nurses and other mothers); and difficulties faced (distance to NCU, inadequate guidance and information, and lack of supportive environment)Conclusion: The hospitalization of preterm newborns in NCUs was usually stressful situation for mothers. Their positive experience and coping was related with provided guidance support and involvement in newborn care. Therefore, nurses working in NCU should consider these care components in their practice.